(untitled) (Bangladesh Journal of Nutrition, 2018)
A cross-sectional study was conducted among the inhabitants of the Ward 27 (Bashaboo) of Dhaka Metropolitan City. Out of 52000 people (+20 years, according to the voter list), a total of 450 subjects were selected for interview by purposive sampling. Subjects were categorized as nondiabetic, NDM (n=166) and diabetic, DM (n= 284) groups. The DM group was further categorized after data collection into previously diagnosed diabetes mellitus, DMPD (n= 117) and newly diagnosed diabetes mellitus, DMND (167). Sociodemogrphic, clinical, anthropometric, biochemical, and dietary data were collected using standardized protocols. The findings showed that majority of the respondents were female (60.3%) and belonged to middle income group (Tk 5000-14999) (62.4%). The main clinical complications of the respondents were hypertension (DMPD=26% and DMND=21%), vertigo (DMPD=22% and DMND=27%), joint pain (DMPD=22% and DMND=21%), back pain (DMPD=18% and DMND=20%) and cataract (DMPD=12% and DMND=12%). The level of plasma triglyceride, plasma cholesterol and urine n-albumin were significantly higher among the newly diagnosed DM subjects. The group of middle aged and middle income subjects had significantly higher level of these parameters. The data, therefore, indicate that diabetic related complications among DMND subjects were relatively higher compared to DMPD subjects thus pointing to the notion of a positive effect of a controlled life-style among DMPD patients as per the medication guideline. Bangladesh J. Nutr. Vol. 28-31, December 2018, P: 47-53